2009
DOI: 10.1108/00907320911006985
|View full text |Cite
|
Sign up to set email alerts
|

Library participation in a campus‐wide teaching program

Abstract: PurposeThe purpose of this paper is to chronicle the participation of the Colorado State University Libraries in a campus‐wide teaching program sponsored by the campus center for teaching and learning, and discusses the opportunities provided by such participation for academic librarians in general.Design/methodology/approachThe author uses a case study approach to explore one academic library's participation in a campus‐wide teaching program sponsored by the institution's center for teaching and learning. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 10 publications
0
4
0
Order By: Relevance
“…Moreover, researchers conducting a study of 788 Canadian library staff with instructional responsibilities found that many used self-directed or self-selected postgraduate professional learning experiences (e.g., attending workshops, reviewing the literature) or informal job-based learning offerings to prepare for their teaching responsibilities (Julien & Genuis, 2011). Other scholars have focused on how librarians have used such resources, including job-embedded professional learning (Click & Walker, 2010;Nichols Hess, 2016;Shamchuk, 2015;Walter, 2006), instruction-centric institutional offerings (Hoseth, 2009;Otto, 2014), and a variety of professional mentorship relationships (James, Rayner, & Bruno, 2015;Lorenzetti & Powelson, 2015;Mavrinac, 2005) to support their own teaching identity development. These researchers' works emphasize that academic librarians only begin to learn the pedagogical essentials after they earn Master's of Library or Information Science (MLIS) degrees.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Moreover, researchers conducting a study of 788 Canadian library staff with instructional responsibilities found that many used self-directed or self-selected postgraduate professional learning experiences (e.g., attending workshops, reviewing the literature) or informal job-based learning offerings to prepare for their teaching responsibilities (Julien & Genuis, 2011). Other scholars have focused on how librarians have used such resources, including job-embedded professional learning (Click & Walker, 2010;Nichols Hess, 2016;Shamchuk, 2015;Walter, 2006), instruction-centric institutional offerings (Hoseth, 2009;Otto, 2014), and a variety of professional mentorship relationships (James, Rayner, & Bruno, 2015;Lorenzetti & Powelson, 2015;Mavrinac, 2005) to support their own teaching identity development. These researchers' works emphasize that academic librarians only begin to learn the pedagogical essentials after they earn Master's of Library or Information Science (MLIS) degrees.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Still in her home department within the library, she had space and resources within the center and was publicly listed as a member of its staff. Hoseth (2009) has considered how librarians in this context can work with other educational developers to help disciplinespecific faculty or even entire programs design effective pedagogies for library research and other information literacy skills. Beyond this traditional subject matter, though, this more focused role of librarian as developer meant that she had to develop deeper knowledge of SoTL, ready like educational developers for "practices require that we 'know in' [not just 'know about'] that discipline by participating in shared problem solving, discussions, debates, and commitment to learning and teaching" (Taylor, 2010, p. 60).…”
Section: Librarian As Developer Of the Scholarship Of Teaching And Lementioning
confidence: 99%
“…Librarians are included in this learning ecology model and are identified as a vital resource for their knowledge and experience in successfully integrating library resources and research skills into class assignments. Furthermore, CSU librarians have a long history of collaborating with TILT (Hoseth, 2009). Librarians have contributed to TILT by compiling information sources, designing research guides, participating in resource fairs, teaching short courses, providing workshops about designing effective library assignments, and teaching critical thinking skills.…”
Section: A Faculty-librarian Partnership Through a Learning And Teachmentioning
confidence: 99%